The Demand for Financial Assets in Pakistan (The Pakistan Development Review, 1994)
In recent years Pakistan has moved to liberalise its financial and capital markets. Consequently the reforms will place heavy demand on the instruments of monetary policy to regulate the working of financial markets. Interest rate policy as a component of monetary policy not only determines the allocation of resources between assets but also within each class of assets. Given the scant research on intra-asset response to intertemporal interest rate movements, the present paper fills the gap by studying the determinants of financial assets and quantifies intra-asset substitutability within a system-wide portfolio framework. Using a simplified version of Brainard and Tobin (1968) model, we explain the asset holdings in terms of wealth and interest rates. We test the model on quarterly holdings of five assets, i.e., saving and fixed deposits, khas deposits, national deposit certificates and defence saving certificates. Asset substitutability is ascertained by single equation OLS, FIML (Iterative 3SLS) and restricted FIML estimation techniques. The system-wide restricted model performs according to a priori expectations. Own interest rate effect is positive and significant in three of the four equations. Five of the six off-diagonals are negative, and three are statistically significant. Saving and fixed deposits exhibit weak complementarity. Khas deposit and national deposit certificates are strong substitutes. The model is also used to decompose the change in portfolio share due to wealth, interest rate and residual components.